Emotional Well-Being and Happiness Among Musicians and Non-Musicians - Keerthana Putheri Mohandas Unni; Vigraanth Bapu K. G (International Journal of Indian Psychȯlogy, 2022)
Emotional well-being refers to the emotional quality of an individual’s everyday experience, the frequency and intensity of experiences of happiness, joy, stress, sadness, anger, and affection that make one’s life pleasant or unpleasant. Music can be effectively emitting a response that creates a feeling of pleasure has been proved empirically. The present research aims to study the relationship between emotional wellbeing and happiness in musicians and non-musicians. The research is a non-experimental quantitative research design and for fulfilling this purpose, Warwick Edinburgh Mental Well-being scale (WEMWBS) and Oxford Happiness Questionnaire (OHQ) was administered  on a sample of 144 participants, from the age 18-25. The sample consisted of 99 non-musicians and 44 musicians. The normalcy test has been found that the test is non parametric, thus Mann Whitney U test has been used. Also, Spearman’s Rank correlation was used to find the correlation of emotional well-being and happiness among musicians and non-musicians. The findings indicated that, even though there is no significant difference in both happiness as well as emotional well-being among musicians and non-musicians, it was found that there is a significant relationship between emotional well-being and happiness in Musicians as Non-musicians.